Constructing a precise radio map and application of indoor positioning with dual-frequency Wi-Fi fingerprinting method. (15th October 2020) - Ozdemir, Behlul Numan; Ceylan, Ayhan
Highlights: Wi-Fi fingerprinting method benefits from single source dual-frequency WAPs. Thresholding can often ignore useful information. Using a measurement tool ensures precise intervals also accurate calibration points. Abstract: Location-based services provide information about objects and people primarily including their location. While their location can be easily estimated outdoors using GNSS, satellite signals are unable to reach indoor spaces such as buildings. Thus, to provide the position information indoors, several technologies have been proposed. Wi-Fi, which is a wireless communication technology offers a wide range of applications for indoor positioning. One of them is the fingerprinting method that uses the diversity of RSS measurements from different wireless access points for each location in indoor space. Here, we constructed a precise radio map with a measuring tool and compared the 2.4 GHz and 5 GHz frequencies with the dual-band fingerprint dataset. Experimental results show that, even if they do not represent a different location, the incorporation of these two frequencies with different characteristics into a single fingerprint dataset improves the overall positioning accuracy.